2014
DOI: 10.1016/j.healthplace.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between urban sprawl and physical activity, obesity, and morbidity – Update and refinement

Abstract: Developing urban and suburban areas in a more compact manner may have some salutary effect on obesity and chronic disease trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
176
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(202 citation statements)
references
References 47 publications
19
176
0
7
Order By: Relevance
“…In addition, a recent study has found that urban sprawl holds down upward intergenerational mobility [24]. As regards health, adults living in sprawling metropolitan areas tend to walk less, are more obese, and suffer more from high blood pressure [25]. Urban sprawl may provide more housing choices for residents, but more centralized metropolitan areas actually exhibit lower median home prices and lower proportions of homes in upper-end price categories than sprawling regions [26].…”
Section: Research Background and Progressmentioning
confidence: 99%
“…In addition, a recent study has found that urban sprawl holds down upward intergenerational mobility [24]. As regards health, adults living in sprawling metropolitan areas tend to walk less, are more obese, and suffer more from high blood pressure [25]. Urban sprawl may provide more housing choices for residents, but more centralized metropolitan areas actually exhibit lower median home prices and lower proportions of homes in upper-end price categories than sprawling regions [26].…”
Section: Research Background and Progressmentioning
confidence: 99%
“…Muchos estudios han puesto de manifiesto cómo la morfología urbana se relaciona con la actividad física (Savitch 2003;Ewing et al 2008Ewing et al , 2014Seliske, Pickett, and Janssen 2012;Berrigan et al 2014). Así en el estudio realizado por se observó cómo la población que residía en áreas más dispersas caminaba poco y tenía un Índice de Masa Corporal alto (prácticamente 0.085 kg/m2), mientras la población que residía en áreas más compactas caminaba más y tenía un Índice de Masa Corporal bajo (tabla 1).…”
Section: Indicadores Urbanísticos Relacionados Con La Actividad Físicaunclassified
“…El impacto más controvertido del fenómeno de la dispersión urbana es su influencia en la elección de modos de transporte específicos (Travisi, Camagni, and Nijkamp 2010). La proliferación de áreas urbanas de baja densidad, con predominio de usos de suelo segregados y escasez de servicios en proximidad, ha aumentado las distancias al área urbana central (Zhao et al 2010), reduciendo las posibilidades para realizar desplazamientos no motorizados (Bahrainy y Khosravi, 2013;Brown et al, 2013;Ewing et al, 2014;García-Palomares, 2010;Jerrett et al, 2013).…”
Section: Introductionunclassified